Determinants of Poor Blood Pressure Control in Hypertensive Patients: Findings from the Baseline Survey in West Bank, Palestine - Anan Jarab; Hamzeh Al Zabadi; Hussein Hallak; Maher Khdour; Qusai Al-Shahed; Tareq Mukattash (My University, 2017)
Determinants of Poor Blood Pressure Control in Hypertensive Patients: Findings from the Baseline Survey in West Bank, Palestine